A Study of the Effectiveness of Webinars in the National Movement to Eradicate Gambling and Illegal Online Loans - Lubis, Muharman; Fauzan, Ratandi Ahmad (Jurnal Pengabdian Bakti Akademisi, 2025)
The rise of illegal online gambling (judol) and digital loan fraud (pinjol) has become a severe socio-economic problem in Indonesias digital era, threatening public welfare and economic stability. This community service program, entitled Gerakan Nasional Berantas Judi Online dan Pinjaman Online Ilegal (National Movement to Eradicate Online Gambling and Illegal Loans), was designed as a preventive educational initiative to strengthen public awareness and digital literacy. The activity employed a service learning approach through an online webinar format involving 91 participants from academic, professional, and public sectors. A quasi-experimental one-group pretest-posttest design was applied to evaluate the interventions effectiveness using quantitative and qualitative analysis.The results indicated a significant improvement in participants understanding of digital crime risks, with the average post-test score increasing by 9.2 percentage points from the pre-test results. Qualitative responses also revealed enhanced awareness of the legal, social, and psychological impacts of online gambling and illegal loans. This activity contributes to achieving Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 3 (Good Health and Well-being), and SDG 16 (Peace, Justice and Strong Institutions). Overall, the webinar effectively served as a model for community-based digital literacy programs, demonstrating that academic institutions can play a strategic role in preventing digital financial crimes through inclusive, technology-driven education.